Appearance of QRS fragmentation late after Mustard/Senning repair is associated with adverse outcome. Issue 13 (9th February 2017) - Helsen, Frederik; Vandenberk, Bert; De Meester, Pieter; Van De Bruaene, Alexander; Gabriels, Charlien; Troost, Els; Gewillig, Marc; Meyns, Bart; Willems, Rik; Budts, Werner
Abstract : Objective: To evaluate if development of fragmented QRS (fQRS) complexes, a marker of inhomogeneous ventricular activation due to myocardial fibrosis, is associated with adverse outcome in adults after Mustard/Senning repair for d-transposition of the great arteries (d-TGA). Methods: Adults with atrial switch repair for d-TGA were selected from the database of a tertiary care hospital. Exclusion criteria were systemic right ventricular (RV) assist device or heart transplantation (HTx) before the age of 16, or fQRS already present at first visit to the Adult Congenital Heart Disease clinic. A blinded expert reader retrospectively analysed all available ECGs after the age of 16 for the presence of fQRS. The appearance of fQRS was modelled for each patient as a time-dependent variable. Cox regression was performed to assess the relationship between covariates and the composite endpoint of cardiovascular mortality, HTx or systemic RV assist device. Results: Records of 89 patients (34% female, 42% Mustard repair) were analysed. At latest follow-up, fQRS was noted in 26 patients (29%). Over a median follow-up time of 16.9 (IQR 12.6–22.9) years, the composite endpoint occurred in nine patients (10%). In multivariable Cox analysis, appearance of fQRS (HR 14.11; 95% CI 1.42 to 140.12) and development of severe RV dysfunction (HR 11.36; 95% CI 2.08 to 62.17) were significantly associated with the composite endpoint. Conclusions: Appearance of fQRS complexes on a 12-lead ECG is associated with adverse outcome in adults after atrial switch repair for d-TGA. In this population, fQRS detection might be a promising and easily implementable tool to identify patients at risk for adverse events.